Praktek Terbaik dalam Model Kurikulum dan Pembelajaran Pendidikan Islam Tradisional - Kokom Komariah; Dede Rosyada; Iswan; Ahmad Suryadi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Traditional Islamic education, particularly through pesantren, has a rich and important history in the development of Islam in Indonesia since the 7th century AD. Its role is significant in preserving religious identity, advancing knowledge, maintaining the Arabic language, strengthening morality, and perpetuating Islamic culture. The main principles of traditional Islamic education curriculum include monotheism (tauhid), the Quran and Sunnah, religious knowledge, character formation, practical skills, contextualization, and personality development. This research employs literature method and qualitative approach by gathering data from various sources such as books, journals, and digital sources. This allows for a deeper understanding of effective teaching methods including student-centered approaches, experiential learning, technology utilization, and collaboration. The integration of spiritual and intellectual development creates balanced and conscious individuals. Adapting traditional practices into modern education combines cultural values with relevant technology. Preserving the essence of traditional Islamic education in the present era requires deep understanding, integration with modern science, engaged learning, character education, cultural preservation, and teacher development. Thus, traditional Islamic education remains relevant and beneficial for the development of better individuals and society.